## Step 1 :

Equation in ~ the finish of step 1 : ((0 - 24x2) - 40x) - 25

## Step 3 :

Pulling out prefer terms :3.1 traction out choose factors:-16x2 - 40x - 25=-1•(16x2 + 40x + 25)

Trying to factor by separating the middle term

3.2Factoring 16x2 + 40x + 25 The first term is, 16x2 that is coefficient is 16.The center term is, +40x its coefficient is 40.The last term, "the constant", is +25Step-1 : main point the coefficient the the an initial term by the constant 16•25=400Step-2 : discover two factors of 400 whose sum equates to the coefficient the the middle term, i m sorry is 40.

 -400 + -1 = -401 -200 + -2 = -202 -100 + -4 = -104 -80 + -5 = -85 -50 + -8 = -58 -40 + -10 = -50 -25 + -16 = -41 -20 + -20 = -40 -16 + -25 = -41 -10 + -40 = -50 -8 + -50 = -58 -5 + -80 = -85 -4 + -100 = -104 -2 + -200 = -202 -1 + -400 = -401 1 + 400 = 401 2 + 200 = 202 4 + 100 = 104 5 + 80 = 85 8 + 50 = 58 10 + 40 = 50 16 + 25 = 41 20 + 20 = 40 That"s it

Step-3 : Rewrite the polynomial splitting the middle term making use of the two determinants found in step2above, 20 and also 2016x2 + 20x+20x + 25Step-4 : include up the very first 2 terms, pulling out choose factors:4x•(4x+5) include up the critical 2 terms, pulling out typical factors:5•(4x+5) Step-5:Add increase the four terms the step4:(4x+5)•(4x+5)Which is the wanted factorization

Multiplying Exponential Expressions:3.3 multiply (4x+5) by (4x+5)The rule says : To multiply exponential expression which have the same base, include up your exponents.In our case, the typical base is (4x+5) and the index number are:1,as(4x+5) is the exact same number together (4x+5)1and1,as(4x+5) is the same number as (4x+5)1The product is therefore, (4x+5)(1+1) = (4x+5)2